Vitamin C Deficiency in Patients With Acute Myeloid Leukemia - Ottone, Tiziana; Faraoni, Isabella; Fucci, Giorgio; Divona, Mariadomenica; Travaglini, Serena; De Bellis, Eleonora; Marchesi, Francesco; Angelini, Daniela Francesca; Palmieri, Raffaele; Gurnari, Carmelo; Giansanti, Manuela; Nardozza, Anna Maria; et al. (Frontiers in Oncology, 2022)
Vitamin C has been shown to play a significant role in suppressing progression of leukemia through epigenetic mechanisms. We aimed to study the role of vitamin C in acute myeloid leukemia (AML) biology and clinical course. To this purpose, the plasma levels of vitamin C at diagnosis in 62 patients with AML (including 5 cases with acute promyelocytic leukemia, APL), 7 with myelodysplastic syndrome (MDS), and in 15 healthy donors (HDs) were studied. As controls, vitamins A and E levels were analysed. Expression of the main vitamin C transporters and of the TET2 enzyme were investigated by a specific RQ-PCR while cytoplasmic vitamin C concentration and its uptake were studied in mononuclear cells (MNCs), lymphocytes and blast cells purified from AML samples, and MNCs isolated from HDs. There were no significant differences in vitamin A and E serum levels between patients and HDs. Conversely, vitamin C concentration was significantly lower in AML as compared to HDs (p<0.0001), inversely correlated with peripheral blast‐counts (p=0.029), significantly increased at the time of complete remission (CR) (p=0.04) and further decreased in resistant disease (p=0.002). Expression of the main vitamin C transporters SLC23A2, SLC2A1 and SLC2A3 was also significantly reduced in AML compared to HDs. In this line, cytoplasmic vitamin C levels were also significantly lower in AML-MNCs versus HDs, and in sorted blasts compared to normal lymphocytes in individual patients. No association was found between vitamin C plasma levels and the mutation profile of AML patients, as well as when considering cytogenetics or 2017 ELN risk stratification groups. Finally, vitamin C levels did not play a predictive role for overall or relapse-free survival. In conclusion, our study shows that vitamin C levels are significantly decreased in patients with AML at the time of initial diagnosis, further decrease during disease progression and return to normal upon achievement of CR. Correspondingly, low intracellular levels may mirror increased vitamin C metabolic consumption in proliferating AML cells.